Transcending the new woman multiethnic narratives in the Progressive Era - Rich, Charlotte J. (University of Missouri Press, 2009)
"Examines multiethnic women writers' responses to the ideal of the New Woman in America at the dawn of the twentieth century, opening up a world of literary texts that lend new insight, revealing how these authors articulated the contradictions of the American New Woman, and how social class, race, or ethnicity impacted women's experiences"--Provided by publisher.